The relevance of resistance exercise programs on the treatment and prevention of sarcopenia in the elderly: an integrative review (Research, Society and Development, 2021)
Objective: To analyze the effects of resistance exercise programs in the treatment and prevention of sarcopenia in the elderly, in order to demonstrate the importance and relevance of the intervention. Methodology: This is an integrative literature review with a qualitative approach. Articles published between 2016 and 2021 were selected. The survey was carried out on the platforms: Scientific Electronic Libray Online (Scielo), National Library of Medice (PubMed), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Academic Google. Results and discussion: 8 articles were selected to compose the analysis. Resistance exercises proved to be essential for the quality of life of the elderly, as it delays sarcopenia. In studies that included resistance exercise alone or combined with aerobic exercise, improvements in muscle mass, muscle strength, and functional test performance were observed. Studies have shown that resistance exercise programs have great chances of providing positive results, both in the prevention and treatment of sarcopenia, being considered excellent alternatives to reduce the evolution of the sarcopenic geriatric syndrome. Conclusion: The studies found show that resistance exercise produces excellent results, promoting both prevention and rehabilitation of sarcopenia in the elderly, acting directly in the reversal or attenuation of the syndrome, by promoting anatomical and physiological adaptations, such as increased muscle mass and strength. In this case, physiotherapy aims to gain and maintain muscle strength, improve the performance of daily activities, improve balance and reduce the risk of falls and fractures.